The Picot report and the legitimation of education policy : a thesis presented in partial fulfilment of the requirements for the degree of Master of Educational Administration at Massey University - Wilson, Kenneth James (Massey University, 1990)
This is a study of the formation of an educational policy. It focuses on the use, by the state, of an individual policy document. The study is theoretically located within the framework of policy analysis, a field of study within the sociology of education. It is argued that the state's response to a fiscal crisis exposes its giving of policy priority to the strategies of accumulation and legitimation. The study illuminates the elitist and technocratic policy formation process adopted by the Government for its review of the administration of education. It is argued that the policy and construction of the Picot Report was the means by which the state sought to legitimise its education policies by organising consent for them in civil society. The study applies concepts which come from recent extensions of neo-marxist analyses of the state to the policy formation process to investigate the limits and capacity of the state to act in policy formation. The role of a small goup of state officials in the construction of the discourses and the management of the policy formation process through which the Report was constructed is described. A materialist concept of language is applied to the policy text in order to illuminate the source of the historically specific discourses from which the text was constructed. An account is given of the construction of the Report. It is argued that a policy text is neither value free nor possessed of a single unambiguous meaning. The assertion is tested empirically by interviewing a sample of those involved in the construction of the Picot Report and examining their responses to establish that a variety of readers of a policy text will create a variety of meanings, even at the level of those who constructed the text. In this way the Picot Report is deconstructed and its constituent discourses arc revealed.
Keywords: Education policy; Educational administration; Government policy; Picot Report